2011
DOI: 10.1038/ajh.2011.37
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Social Context to Blood Pressure: Findings From a Multilevel Analysis of Social Capital and Systolic Blood Pressure

Abstract: To the best of our knowledge, this study is the first to investigate the association between social capital and systolic blood pressure by using a multilevel methodological framework. Surprisingly, we found that lack of fairness had a strong effect on systolic blood pressure. However, we could not find any significant associations between other items of social capital and systolic blood pressure. Further studies are needed to clarify the mechanism by which lack of fairness may have an effect on systolic blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 12 publications
(23 reference statements)
1
26
0
Order By: Relevance
“…32 These mistrustful social relationships are an important source of stress for all groups in society and have been associated with a higher level of systolic blood pressure. 42 Second, unfair treatment and stigmatization have also been associated with increased risk of high blood pressure. 43,44 As people who have been displaced move into the city and encounter the types of unfair treatment and stigmatization described in these interviews, they may experience social isolation and chronic stress that, ultimately, contribute to increased risk of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…32 These mistrustful social relationships are an important source of stress for all groups in society and have been associated with a higher level of systolic blood pressure. 42 Second, unfair treatment and stigmatization have also been associated with increased risk of high blood pressure. 43,44 As people who have been displaced move into the city and encounter the types of unfair treatment and stigmatization described in these interviews, they may experience social isolation and chronic stress that, ultimately, contribute to increased risk of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible mediators between social capital and mortality are psychological distress and hypertension. A study from Japan found that lower social capital, measured by trust, was associated with psychological distress in the elderly (Hamano et al, 2011b), and that systolic blood pressure increased with an increasing perception of lack of fairness, after adjustment for individual confounders in a multilevel framework (Hamano et al, 2011a). Poor self-rated health is associated with increased mortality and it may represent another potential mediator between social capital and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…During the past decades, there has been an upsurge of interest in the concept social capital and it has been referred to as a societal component that is positively associated with democracy (Putnam, 2000b;Putnam, 1993) and economic wealth (Holzmann et al, 1999;Woolcock et al, 2000). In contrast, lack of social capital has been associated with social disintegration and violent crime (Sampson et al, 1997) as well as adverse health-related outcomes in all ages (Green et al, 2000;Hyyppä et al, 2001;Kawachi et al, 1997a;Sundquist et al, 2006), such as poor selfrated health (Kawachi et al, 1999;Sundquist et al, 2007), poor mental health (Hamano et al, 2010;Lofors et al, 2007), hypertensive status (Hamano et al, 2011a) and coronary heart disease (Sundquist et al, 2006). Current definitions and measurements of social capital have usually been derived from leading social scientists such as Bourdieu, Coleman and Putnam.…”
Section: Introductionmentioning
confidence: 99%
“…The social capital mechanism suggests that inequality is socially corrosive and leads to social conflict and increasing levels of mistrust between groups with greater and those with fewer resources 9,13 . There is some empirical support for this pathway, with one recent study concluding that social capital, assessed as a contextual phenomenon, may reduce blood pressure through decreasing chronic stress or increasing the modulation of stressful events 15 .…”
Section: Introductionmentioning
confidence: 99%